EFEKTIVITAS TERAPI MUSIK INSTRUMENTAL TERHADAP TINGKAT KECEMASAN MAHASISWA FAKULTAS TEKNIK UNIVERSITAS RIAU KEPULAUAN DALAM MENYUSUN SKRIPSI - Isramilda; Fitta Deskawaty; Arin Vela Zhafira (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2023)
Background: Anxiety is a diffuse and vague concern caused by an unknown or non-existent threat. Anxiety in students can arise in the preparation of undergraduate thesis due to internal and external factors. The purpose of this study was to analyze the effectiveness of instrumental music therapy on the anxiety level of engineering students at the University of Riau Islands in preparing undergraduate thesis in 2023 Methods: This research method uses a Quasi-Experimental methodology with a Non Equivalent Control Group Design. The sampling technique in this study was purposive sampling technique with the Slovin formula and obtained a total sample of 68 respondents. This data was collected using the Zung Self Rating Anxiety Scale questionnaire and then processed using the Wilcoxon Signed Rank Test, which is to measure the level of significance of the difference between two groups of paired data on an ordinal scales. Results: The results of the analysis with the Wilcoxon Signed Rank Test showed a significant difference between the control group and the experimental group, namely p = 0.000 (p <0.05). In the mean rank column of the experimental group is higher (16.50) than the control group (4.50). Conclusion: Based on the results of the research there is the effectiveness of music therapy on the anxiety level of Engineering Faculty students at the University of Riau Islands in preparing their undergraduate thesis in 2023.